Blink twice [videorecording (Blu-Ray)] - Kravitz, Zoë, 1988-; Kravitz, Zoë, 1988-; Feigenbaum, E. T.; Tatum, Channing; Ackie, Naomi; Slater, Christian; Rex, Simon, 1974-; Arjona, Adria, 1992-; MacLachlan, Kyle, 1959-; Osment, Haley Joel, 1988-; Davis, Geena; Shawkat, Alia, 1989-; et al. (Warner Bros Entertainment Inc., 2024)
When tech billionaire Slater King meets cocktail waitress Frida at his fundraising gala, he invites her to join him and his friends on a dream vacation on his private island. As strange things start to happen, Frida questions her reality. There is something wrong with this place. She'll have to uncover the truth if she wants to make it out of this party alive.